PENGARUH PMDN, PMA, PENGELUARAN PEMERINTAH DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI - Fiorentina, Risma Fahrella; Ajeng Kartika Galuh (Journal of Development Economic and Social Studies, 2024)
Central Java is a province on the island of Java that is experiencing relatively low economic growth. Even though Central Java Province has sufficient potential to support economic growth. Therefore, researchers in this study will identify whether there is influence of Foreign Investment, Domestic Investment, Workforce, and Government Expenditures on Economic Growth in Central Java. This research focuses on districts/cities in Central Java province. The data in this study were obtained from the Central Bureau of Statistics (BPS). To find out whether these variables affect economic growth in Central Java, panel data regression analysis is used. This research produces PMDN, Government Expenditures, and Labor which have a positive and significant effect on Economic Growth in Central Java.